Bruise injury and its effect on 'Carabao' mango fruit quality - Lacap, Angelyn T.; Bayogan, Emma Ruth V.; Secretaria, Liezel B.; Joyce, Daryl C.; Ekman, Jennifer H.; Goldwater, Adam D. (Vol. 150, No. 6B (December 2021) pages 1689-1701.)
Poor handling results in bruising which translates into losses for the Philippine 'Carabao' mango fruit industry. This study determined bruise injury in 'Carabao' fruit as affected by harvest method, dropping from heights of up to 5m, and interaction of ripeness stage [viz mature green (MG), more yellow than green (MYG), and fully yellow (FY)] and dropping from 0.5 m up to 1.5. -Title page.